Identitas dalam Pergolakan: Fenomenologi Hijrah pada Punk Muslimah - Firmansyah, Mursyidul Haq; Hairuddin Cikka; Taufik (Musawa: Journal for Gender Studies, 2025)
This research aims to understand the hijrah experience experienced by Muslim punk women through a phenomenological approach. Hijrah, in this context, is not just a physical change or lifestyle, but an existential process in building a new meaning of life and identity. Muslim punks are at the crossroads of two culturally conflicting worlds: a punk subculture steeped in the spirit of resistance, and Islamic values that emphasize spiritual obedience. Through in-depth interviews with several participants, it was found that the process of migration involves identity conflicts, self-reflection, and complex negotiation of meaning. The informants did not necessarily abandon their old identities, but rather reconstructed punk values within the framework of religiosity. Critical spirit, honesty to oneself, and social awareness are maintained, but directed towards deeper spiritual struggles. The main findings show that hijrah is a medium of authenticity transformation, where Muslim punks try to live more honestly to their deepest beliefs. A new identity as a Muslim woman does not erase the past, but becomes a continuation of the process of more complete self-formation. Thus, hijrah is not a form of rejection of an old identity, but the discovery of a new meaning that comes from past experiences and current spiritual beliefs.